Phylogenetic affiliation of endophytic actinobacteria associated with selected orchid species and their role in growth promotion and suppression of phytopathogens - Saikia, Juri; Mazumdar, Rajkumari; Thakur, Debajit (Frontiers in Plant Science, 2022)
Endophytic actinobacteria aid in plant development and disease resistance by boosting nutrient uptake or producing secondary metabolites. For the first time, we investigated the culturable endophytic actinobacteria associated with ten epiphytic orchid species of Assam, India. 51 morphologically distinct actinobacteria were recovered from surface sterilized roots and leaves of orchids and characterized based on different PGP and antifungal traits. According to 16S rRNA gene sequence, these isolates were divided into six families and eight genera, where Streptomyces was most abundant (n=29, 56.86%), followed by Actinomadura, Nocardia, Nocardiopsis, Nocardioides, Pseudonocardia, Microbacterium, and Mycolicibacterium. Regarding PGP characteristics, 25 (49.01%) isolates demonstrated phosphate solubilization in the range of 61.1±4.4 - 289.7±11.9 µg/ml, whereas 27 (52.94%) isolates biosynthesized IAA in the range of 4.0±0.08 - 43.8±0.2 µg/ml, and 35 (68.62%) isolates generated ammonia in the range of 0.9±0.1 - 5.9 ±0.2 µmol/ml. These isolates also produced extracellular enzymes, viz. protease (43.13%), cellulase (23.52%), pectinase (21.56%), ACC deaminase (27.45%), and chitinase (37.25%). Out of 51 isolates, 27 (52.94%) showed antagonism against at least one test phytopathogen. In molecular screening, most isolates with antifungal and chitinase producing traits revealed the presence of 18 family chitinase genes. Two actinobacterial endophytes, Streptomyces sp. VCLA3 and Streptomyces sp. RVRA7 were ranked as the best strains based on PGP and antifungal activity on bonitur scale. GC-MS examination of ethyl acetate extract of these potent strains displayed antimicrobial compound phenol, 2,4-bis-(1,1-dimethylethyl) as the major metabolite along with other antifungal and plant growth beneficial bioactive chemicals. SEM analysis of fungal pathogen F. oxysporum (MTCC 4633) affected by Streptomyces sp. VCLA3 revealed significant destruction in the spore structure. An in vivo plant growth promotion experiment with VCLA3 and RVRA7 on chilli plants exhibited statistically significant (p<0.05) improvements in all of the evaluated vegetative parameters compared to the control. Our research thus gives insight into the diversity, composition, and functional significance of endophytic actinobacteria associated with orchids. This research demonstrates that isolates with multiple plant development and broad-spectrum antifungal properties are beneficial for plant growth. They may provide viable alternative to chemical fertilizers and pesticides and a sustainable solution for chemical inputs in agriculture.